Diskursus Relasi Agama dan Negara dalam Kanal Youtube Aswaja NU Center Jawa Timur: Religion and State in Youtube: Understanding the Discourse in Aswaja NU's Channel - Marasabessy, Nabila (ETTISAL : Journal of Communication, 2024)
The debate about the relationship between religion and the state in Indonesia has been going on since pre-independence times and the problem is still ongoing today. This debate occurred in various public spaces, including on social media, YouTube channels. Aswaja NU Center East Java is Nahdlatul Ualama's YouTube channel which also articulates discourse on the relations between religion and the state in Indonesia. The aim of this research is to find out how the relationship between religion and the state in Indonesia is interpreted on the Aswaja NU Center East Java YouTube channel and to find out the causes of this discourse continues to this day. This research approach is qualitative using Norman Fairclough's Critical Discourse Analysis method. This method analyzes discourse from linguistic aspects, aspects of discourse practice and the surrounding social context. The results of the research show that according to the East Java Aswaja NU Center, the most appropriate form of relationship between religion and the state to be implemented in Indonesia is the substantive model, namely the State prioritizes the implementation of religious values ​​in state life rather than the existence of religious symbols. Then the factor that causes the debate on the relationship between religion and the state in Indonesia continues to rage, namely because there is a history of the formulation of the basic state of Pancasila which has not been completed and Pancasila is still used as a political tool of the ruling regime.